2019
DOI: 10.3390/ma12101678
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on the Preparation of Recycled Admixtures by Using Construction and Demolition Waste

Abstract: The use of construction and demolition waste (CDW) to prepare recycled admixtures is of great significance for the complete resource reutilization of CDW. In this paper, different kinds of CDW were prepared into recycled powder (RP) with a specific particle size (0–45 µm or 0–75 µm). The fineness, water requirement ratio (WRR), fluidity, loss on ignition (LOI), strength activity index (SAI) and compatibility of cement and superplasticizer (CCS) were examined. The above test results were analyzed by advanced an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…Further to the X-ray fluorescence (XRF)-determined chemical composition of the GRC and OPC shown in Figure 1a, the major oxides were SiO 2 (46.10 wt%) and CaO (40.0 wt%). The figure also presents graphically the minimum and maximum ground concrete replacement ratios used in earlier studies [20][21][22][23][24][25][26] on pastes, mortars and concrete.…”
Section: Bindersmentioning
confidence: 99%
“…Further to the X-ray fluorescence (XRF)-determined chemical composition of the GRC and OPC shown in Figure 1a, the major oxides were SiO 2 (46.10 wt%) and CaO (40.0 wt%). The figure also presents graphically the minimum and maximum ground concrete replacement ratios used in earlier studies [20][21][22][23][24][25][26] on pastes, mortars and concrete.…”
Section: Bindersmentioning
confidence: 99%
“…Figure 2b shows the XRD results, whereby the SiO 2 content in RBP is much higher than that in cement and FA, and there are no hydrated compounds (such as CaO, Ca(OH) 2 ) in RBP. Attributed the SiO 2 being the main component that takes part in the pozzolanic reaction of cementitious materials, the high fineness RBP can be used as the SCM in the cementitious materials [40]. Figure 2b further shows the SEM images of RBP, and an irregular micro-structure can be observed.…”
Section: Micro-properties Of the Cementitious Materials Containing Rbpmentioning
confidence: 91%
“…Previous studies demonstrated that the RCF exhibited potential reactivity, which can be used for new concrete production [ 21 ]. However, the workability, strength, and durability of concrete containing RCF would significantly decrease due to the high porosity and low reactivity of RCF [ 22 , 23 , 24 ]. Therefore, only a minimal amount of RCF can be utilized, and the rest is disposed of by landfilling and dumping, failing to take full advantage of waste resources and causing environmental and groundwater pollution [ 2 , 19 ].…”
Section: Introductionmentioning
confidence: 99%